2020
DOI: 10.1007/s11096-020-01178-y
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of stroke and medication adherence among patients with recurrent stroke or transient ischemic attack in Indonesia: a multi-center, cross-sectional study

Abstract: BackgroundThere is a limited data in Indonesia regarding the stroke knowledge and medication adherence among stroke survivors.ObjectiveTo assess the level of stroke knowledge and medication adherence along with their relationship among stroke survivors.SettingTwo tertiary-care hospitals in Surabaya, East Java, Indonesia.MethodsA prospective, cross-sectional study was conducted among 215 stroke survivors. Stroke Knowledge Test and the Morisky Green Levine Adherence Scale questionnaires were used to evaluate str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Effective pharmacotherapy and optimal medication adherence are necessary to prevent secondary stroke. A recent study showed that optimal medication adherence rate is suboptimal among stroke survivors (30). Findings from our study clearly documented that clinical pharmacist-led educational intervention which include medication adherence and knowledge of stroke and medications improved medication adherence in patients with low adherence.…”
Section: Discussionsupporting
confidence: 71%
“…Effective pharmacotherapy and optimal medication adherence are necessary to prevent secondary stroke. A recent study showed that optimal medication adherence rate is suboptimal among stroke survivors (30). Findings from our study clearly documented that clinical pharmacist-led educational intervention which include medication adherence and knowledge of stroke and medications improved medication adherence in patients with low adherence.…”
Section: Discussionsupporting
confidence: 71%
“…The study conducted by Ahmadi and Ogren was telephone-based, the study conducted by Lakshminarayan, Yan, and Sarfo used an integrated health application on the smartphone, while the study conducted by Kim used a combination of telephone, application, and messaging services [11,15,[18][19][20][21]. Studies have shown that poor self-management of stroke risk factors, low stroke knowledge, and poor adherence to medication are the potential causes of recurrent stroke [22]. The better outcome of the telemedicine intervention group is probably due to the fact that telemedicine can improve stroke risk factors management and drug compliance.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that patients who have had two or more strokes have better drug compliance. This may be because the patients' clinical outcome becomes worse after a stroke recurrence, which increases their awareness and attention to the role of drugs in secondary prevention ( 21 , 44 ). Similarly, patients with severe consequences may obtain more obvious benefits or relief from medication and are therefore more likely to receive prescription medication ( 21 ).…”
Section: Discussionmentioning
confidence: 99%